Fair-Weather Near-Surface Atmospheric Electric Field Measurements at the Zhongshan Chinese Station in Antarctica - Lei Li; Tao Chen; Shuo Ti; Shi-Han Wang; Jia-Jun Song; Chun-Lin Cai; Yong-Hua Liu; Wen Li; Jing Luo (Applied Sciences, 2022)
The variability in the atmospheric electric field is modulated by a combination of solar activities, meteorological activities, and geological conditions. A foundational dataset of the daily variations in the fair-weather atmospheric electric field is established in this study, and several examinations are conducted into the details of these variations in particular regions. This paper is organized as follows. First, the researchers count the datasets of daily variations to the atmospheric electric field on fair-weather days from 1 March–1 August 2022 at Zhongshan Chinese Station in Antarctica and Changping Station in Beijing. Then, the average daily variation in the atmospheric electric field on 40 fair-weather days in Antarctica is shown and the variations are compared with the average curve of 37 fair-weather days in Beijing during the same time period. Finally, the three main differences between these variations, their possible reasons, and a reasonable error analysis are clarified and discussed at the end of this paper.